2023
DOI: 10.1093/abm/kaad012
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Efficacy of a Theory-Informed Intervention to Increase COVID-19 Testing Uptake Among People Who Inject Drugs in San Diego County: Findings From a Pilot Randomized Controlled Trial

Abstract: Background People who inject drugs (PWID) have low rates of COVID-19 testing yet are vulnerable to severe disease. In partnership with a mobile syringe service program (SSP) in San Diego County, CA, we developed the evidence-, community-, and Social Cognitive Theory-informed “LinkUP” intervention (tailored education, motivational interviewing, problem-solving, and planning) to increase COVID-19 testing uptake among PWID. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Comparison of the 149 participants by condition at enrollment revealed that the 2 study arms were balanced with respect to proportions who were partially vaccinated against COVID-19 and other behavioral characteristics [ 10 ]. However, LinkUP intervention participants were significantly more likely to be younger and to have recently experienced homelessness or food insecurity ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparison of the 149 participants by condition at enrollment revealed that the 2 study arms were balanced with respect to proportions who were partially vaccinated against COVID-19 and other behavioral characteristics [ 10 ]. However, LinkUP intervention participants were significantly more likely to be younger and to have recently experienced homelessness or food insecurity ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We relied on self-report of vaccine uptake behaviors, which may have elicited socially desirable responses. The limited size and scope of this trial preclude further exploration of potential mediators and moderators of intervention effects identified by theory, literature, or our team's previous research (eg, homelessness, which moderated LinkUP effects on the uptake of COVID-19 testing) [ 10 ]. It is possible that during the 6-month follow-up, participants could have received other interventions that influenced their decisions to become vaccinated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations